Point-of-care testing in private pharmacy and drug retail settings: a narrative review - Justine Tin Nok Chan; Van Nguyen; Thuy Ngan Tran; Nam Vinh Nguyen; Nga Thi Thuy Do; H. Rogier van Doorn; Sonia Lewycka (BMC Infectious Diseases, 2023)
Abstract Background Point-of-care testing (POCT) using rapid diagnostic tests for infectious disease can potentially guide appropriate use of antimicrobials, reduce antimicrobial resistance, and economise use of healthcare resources. POCT implementation in private retail settings such as pharmacies and drug shops could lessen the burden on public healthcare. We performed a narrative review on studies of POCTs in low- and middle-income countries (LMICs), and explored uptake, impact on treatment, and feasibility of implementation. Methods We searched MEDLINE/PubMed for interventional studies on the implementation of POCT for infectious diseases performed by personnel in private retail settings. Data were extracted and analysed by two independent reviewers. Results Of the 848 studies retrieved, 23 were included in the review. Studies were on malaria (19/23), malaria and pneumonia (3/23) or respiratory tract infection (1/23). Nine randomised controlled studies, four controlled, non-randomised studies, five uncontrolled interventions, one interventional pre-post study, one cross-over interventional study and three retrospective analyses of RCTs were included. Study quality was poor. Overall, studies showed that POCT can be implemented successfully, leading to improvements in appropriate treatment as measured by outcomes like adherence to treatment guidelines. Despite some concerns by health workers, customers and shop providers were welcoming of POCT implementation in private retail settings. Main themes that arose from the review included the need for well-structured training with post-training certification covering guidelines for test-negative patients, integrated waste management, community sensitization and demand generation activities, financial remuneration and pricing schemes for providers, and formal linkage to healthcare and support. Conclusion Our review found evidence that POCT can be implemented successfully in private retail settings in LMICs, but comprehensive protocols are needed. High-quality randomised studies are needed to understand POCTs for infectious diseases other than malaria.